Changes in, and factors associated with, frequency of sex in Britain: evidence from three National Surveys of Sexual Attitudes and Lifestyles (Natsal). (7th May 2019) - Wellings, Kaye; Palmer, Melissa J; Machiyama, Kazuyo; Slaymaker, Emma
Abstract: Objectives: To examine changes over time in the reported frequency of occurrence of sex and associations between sexual frequency and selected variables. Design: Repeat, cross sectional, population based National Surveys of Sexual Attitudes and Lifestyles (Natsal-1, Natsal-2, and Natsal-3). Setting: British general population. Participants: 18 876 men and women aged 16-59 and resident in Britain were interviewed in Natsal-1, completed in 1991; 11 161 aged 16-44 years in Natsal-2, completed in 2001, and 15 162 aged 16-74 years in Natsal-3, completed in 2012. Comparisons of actual and preferred sexual frequency in men and women aged 16-44 (the age range common to all surveys) between the three surveys. Factors associated with sexual frequency of at least once a week were examined using Natsal-3 data. Main outcome measures: Sexual activity in the past month; frequency of sex in the past month; preferred frequency of sex. Results: Median number of occasions of sex in the past month was four in Natsal-1 and Natsal-2 and three in Natsal-3 among women; and three in Natsal-1, Natsal-2, and Natsal-3 among men. The proportion reporting no sex in the past month fell between Natsal-1 and Natsal-2 (from 28.5% to 23.0% in women and from 30.9% to 26.0% in men) but increased significantly in Natsal-3 (to 29.3% in women and 29.2% in men). The proportion reporting sex 10 times or more in the past month increased between Natsal-1 and Natsal-2, from 18.4% to 20.6% in women and from 19.9% to 20.2% in men, but fell in Natsal-3, to 13.2% in woman and 14.4% in men. Participants aged 25 and over, and those married or cohabiting, experienced the steepest declines in sexual frequency (P values for interaction <0.05). Alongside the declines in sexual frequency, there was an increase in the proportion reporting that they would prefer sex more often. Age adjusted odds ratios showed that men and women in better physical and mental health had sex more frequently, as did those who were fully employed and those with higher earnings. Conclusions: Frequency of sex has declined recently in Britain, more markedly among those in early middle age and those who are married or cohabiting. The findings and their implications need to be explained in the context of technological, demographic, and social change in Britain and warrant further investigation.